The role of kinship in bi-national couples: Intergenerational solidarity in Turkish-German families - Tecklenburg, Rena; Boehnke, Mandy (Frontiers in Sociology, 2022)
Intermarriages, i.e., marriages between people from different ethnic backgrounds, have increased in recent years in many parts of the world and also in Germany. These marriages, often between an immigrant and a native partner, have various implications for family dynamics. To date, research has focused on the causes of ethnic exogamy, partnership quality, and fertility among interethnic couples. Using problem-centered interviews with Turkish-German couples living in Germany, the present study aims to broaden this perspective by looking at kin relationships (modes of interaction, spatial and emotional closeness, assistance and support, agreement on values and responsibilities), which have hardly been studied in bi-national families so far. The study pursues a qualitative research design that allows tracing kinship relations and perceived negotiation processes. Using the intergenerational solidarity typology as an heuristic for the qualitative content analysis the results will provide answers to the question what role kinship networks play in these partnerships and how their possibly different demands are balanced. The analysis of the interviews shows that in most cases the quality of relationships is high in both Turkish and German kinship networks and is characterized by openness and cordiality. As a result, relatives from both sides offer emotional, financial, or childcare support to the interviewed families, but differ in the type of support mainly due to physical proximity. Based on the results, we cannot claim that family cohesion is generally closer on one side of the extended family.